Rebooting Computing: New Strategies for Technology Scaling. - Conte, Thomas M.; Track, Elie; DeBenedictis, Erik (Computer (00189162), 2015)
Year-over-year exponential computer performance scaling has ended. Complicating this is the coming disruption of the "technology escalator" underlying the industry: Moore's law. To fundamentally rethink and restart the performance-scaling trend requires bold new ways to compute and a commitment from all stakeholders.